2008
DOI: 10.1021/ma801465r
|View full text |Cite
|
Sign up to set email alerts
|

Homologous Poly(isobutylene)s: Poly(isobutylene)/High-Density Poly(ethylene) Hybrid Polymers

Abstract: We report on the synthesis of poly(homo-isobutylene) and poly(homo-R-methylstyrene) and the thermal properties of these new polymers. Based on the ring-opening metathesis polymerization (ROMP) of 3,3-dimethylcyclopropene and 3-methyl-3-phenyl-cyclopropene, the respective ring-opened polymers were generated. Several catalytic systems (first-generation (I), second-generation (II), third-generation Grubbs-type (IV) and the Schrock-type initiator Mo(N-2,6-iPr 2 C 6 H 3 )(CHCMe 2 Ph)(OCMe 3 ) 2 (III) were used. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 44 publications
2
49
0
Order By: Relevance
“…Materials : All reagents were purchased from Sigma‐Aldrich and used without further purification. Endo,exo[2.2.1] bicyclo‐2‐ene‐5,6‐dicarboxylic acid dimethylester (monomer A ) and exo‐ N ‐(4,4,5,5,6,6,7,7,7‐nonafluoroheptyl)‐10‐oxa‐4‐azatricyclodec‐8‐ene‐3,5‐dione (monomer D ) were synthesized according to methods reported elsewhere 32–34 . A m D n BCPs were synthesized by sequential ring opening metathesis polymerization of monomer A and subsequently of monomer D using Grubbs 1st generation catalyst [RuCl 2 (PCy 3 ) 2 (CHPh)] in dry CH 2 Cl 2 under argon atmosphere at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Materials : All reagents were purchased from Sigma‐Aldrich and used without further purification. Endo,exo[2.2.1] bicyclo‐2‐ene‐5,6‐dicarboxylic acid dimethylester (monomer A ) and exo‐ N ‐(4,4,5,5,6,6,7,7,7‐nonafluoroheptyl)‐10‐oxa‐4‐azatricyclodec‐8‐ene‐3,5‐dione (monomer D ) were synthesized according to methods reported elsewhere 32–34 . A m D n BCPs were synthesized by sequential ring opening metathesis polymerization of monomer A and subsequently of monomer D using Grubbs 1st generation catalyst [RuCl 2 (PCy 3 ) 2 (CHPh)] in dry CH 2 Cl 2 under argon atmosphere at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…7 Shortly after this, Faust and Kennedy et al reported the first living carbocationic polymerization of isobutylene (IB); 8 this breakthrough led to the preparation of well-defined hydroxy-/amino-telechelic PIBs with low dispersity. 13 More recently, Binder et al synthesized poly(homo-isobutylene) from 3,3-dimethylcyclopropene utilizing a similar strategy, 14 and this pseudo-PEIB had a moderate dispersity (1.9-3.9) and a melting temperature (T m ) of 108°C. 9,10 In addition, poly(styrene)-b-poly(iso-butylene)-b-poly(styrene) (SIBS) block polymers have been used as polymeric coatings in a drug-eluting coronary stents.…”
mentioning
confidence: 99%
“…A chemical shift difference of about 1 ppm is expected for cis vs. trans olefins in ROMP polymers (such as polyDCMNBD7b). In a recent report, polyMPCP obtained with a ruthenium-based initiator was assigned to have the trans configuration on the basis of an absorption at ~980 cm −1 and an olefinic 13 CNMR resonance at 136 ppm 21. Therefore the structures of polyMPCP 1 and polyMPCP 3a are assigned as cis , while polyMPCP 2a is assigned to be trans .…”
Section: Resultsmentioning
confidence: 99%